2021
DOI: 10.1177/2333794x21991035
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Iron-Deficiency Anemia in Children Born to Mothers with HIV in Western Kenya

Abstract: The objective of this study was to determine and compare anemia and iron-deficiency anemia (IDA) rates in young Kenyan children who are HIV infected (HI), HIV exposed, uninfected (HEU), and HIV unexposed (HU). Questionnaires, anthropometrics, and blood samples were collected from HI, HEU, and HU aged 18 to 36 months. Descriptive statistics, Fisher’s exact tests, and linear regression were used for analysis. Of 137 total participants, HI (n = 18), HEU (n = 70), and HU (n = 49), 61.1%, 53.6%, and 36.7%, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Iron deficiency anemia is common in children in Kenya, with a prevalence of 26.9% [ 8 ], and there were no features of fibrosis of the liver on imaging of our patient. The patient was discharged with supplementary oral iron with a plan to follow up in the Outpatient Clinic.…”
Section: Case Reportmentioning
confidence: 71%
“…Iron deficiency anemia is common in children in Kenya, with a prevalence of 26.9% [ 8 ], and there were no features of fibrosis of the liver on imaging of our patient. The patient was discharged with supplementary oral iron with a plan to follow up in the Outpatient Clinic.…”
Section: Case Reportmentioning
confidence: 71%
“…A blood sample was taken at enrollment to measure iron-deficiency anemia (IDA) using hemoglobin and serum ferritin. While the primary data regarding IDA is presented elsewhere ( 19 ), this variable was included within the regression analysis, as it is a known risk factor for worse neurodevelopmental outcomes ( 20 ). We classified a child as having IDA if (1) hemoglobin concentration was <118 g/L, based on World Health Organization-published algorithm for individuals living ≥2,000 meters in elevation, consist with local elevation ( 16 ); and (2) ferritin concentrations <12 μg/L.…”
Section: Methodsmentioning
confidence: 99%
“…Even non‐pregnant women had a prevalence of 21.3% for Fe deficiency and 14% for anaemia (Kenya National Micronutrient Survey, 2011 ; Young, 2018 ). Fe deficiency in the pre‐school population living in 60 villages in Western Kenya and North Rift Valley was reported to be 46% (in the year 2012) and 67% (in the year 2021), respectively (Grant et al, 2012 ; Oyungu et al, 2021 ). The 2011 National Micronutrient Survey also found that 83.3% of pre‐school children, 82.3% of non‐pregnant women, 80.2% of school going children, 74.8% of men and 68.3% of pregnant women suffered from Zn deficiency.…”
Section: Iron and Zinc Deficiencymentioning
confidence: 99%